Promoting cognitive health through the nexus of gut microbiota and dietary phytochemicals - Luo, Lin (Frontiers in Nutrition, 2025)
The intricate interactions between gut microbiota and cognitive function have become a forefront topic at the convergence of neuroscience and nutrition. This review systematically evaluates the bidirectional relationship between dietary phytochemicals and gut microbiota, highlighting their potential mechanisms for promoting cognitive health. The review begins by describing how gut microbiota dysbiosis can contribute to cognitive decline by transmitting gut-derived signals to the central nervous system via the gut–brain axis. Subsequently, the discussion focuses on how phytochemicals act as modulators of gut microbiota composition and undergo microbial-mediated metabolic transformation. Special attention is paid to four key microbial-derived metabolites—urolithins, sulforaphane, equol, and hesperidin—that exhibit neuroprotective effects through antioxidative, anti-inflammatory, neuroprotective, and metabolic regulatory pathways. Furthermore, the review examines how individual variability in gut microbiota composition influences the efficiency of phytochemical biotransformation and underscores the implications for precision nutrition interventions. Emerging evidence indicates that the synergistic regulation of the gut–brain axis by dietary phytochemicals and gut microbiota offers a robust theoretical basis for developing novel strategies to preserve cognitive function. Future research should further clarify the molecular mechanisms underlying specific microbe–phytochemical interactions and accelerate the clinical translation of personalized nutrition strategies.